ปริมาณโลหะหนักในแม่น้ำท่าจีนและคลองสาขาตั้งแต่นครชัยศรีถึงปากแม่น้ำท่าจีน - จินตนันท์ วัชรสิงห์ม, Jintanan Watcharasing; วิทย์ ธารชลานุกิจ, Wit Tarnchalanukit; เกษม จันทร์แก้ว, Kasem Junkeaw; นฤชิต ดำปิน, Naruechid dumpin (Naresuan University Journal: Science and Technology (NUJST); Vol 21 No 2 (2013): May-August 2013, 2014)
จากเหตุการณ์น้ำท่วมใหญ่ในพื้นที่ภาคกลางปี2554 แม่น้ำท่าจีนถูกใช้เป็นเส้นทางระบายน้ำส่วนเกินจากแม่น้ำเจ้าพระยาเพื่อระบายออก สู่อ่าวไทย น้ำส่วนเกินที่ถูกระบายผ่านคลองสาขามานี้มีการพัดพาโลหะหนักจากแหล่งกำเนิดมลพิษต่างๆ ลงมายังแม่น้ำท่าจีน หากแหล่งน้ำ ได้รับน้ำทิ้งที่มีการปนเปื้อนโลหะหนักติดต่อกันเป็นเวลานานจะส่งผลต่อคุณภาพน้ำ รวมถึงทำให้เกิดการสะสมของโลหะหนักในห่วงโซ่อาหาร เป็นอันตรายต่อสัตว์น้ำและมนุษย์ได้ ดังนั้น ในการวิจัยครั้งนี้จึงทำการศึกษาปริมาณความเข้มข้นของโลหะหนัก 5 ชนิด ได้แก่ ตะกั่ว แคดเมียม สารหนู ปรอท และนิกเกิล ที่ตรวจพบในตัวอย่างตะกอนดินและน้ำที่เก็บจากแม่น้ำท่าจีนตั้งแต่นครชัยศรีถึงปากแม่น้ำท่าจีน เพื่อศึกษาปริมาณและการสะสมตัวของโลหะหนักที่ไหลลงสู่แม่น้ำท่าจีน เก็บตัวอย่างตะกอนดินและน้ำจากจุดเก็บตัวอย่าง 21 จุด ในแม่น้ำท่าจีนและคลองสาขา (คลองมหาสวัสดิ์ คลองภาษีเจริญ และคลองมหาชัย) คลองละ 5 จุดเพื่อนำมาวิเคราะห์ตามลำดับ โดยแบ่งเป็น 2 ฤดู คือ ฤดูน้ำแล้ง (เมษายน) และฤดูน้ำหลาก (พฤศจิกายน) ในปีเดียวกัน (พ.ศ.2555) ผลการศึกษาพบว่า ตะกั่ว แคดเมียมสารหนู ปรอท และนิกเกิล ในตะกอนดินต่ำกว่าเกณฑ์มาตรฐานตะกอนดินของ NOAA ขณะที่มีเพียงสารหนูที่มีค่าสูงเกินเกณฑ์มาตรฐานคุณภาพน้ำผิวดิน ประเภทที่ 2, 3 และ 4 ของกรมควบคุมมลพิษ ประเทศไทย ซึ่งเป็นโลหะหนักที่สำคัญที่พบในแม่น้ำท่าจีน สำหรับแคดเมียมนั้นไม่พบปนเปื้อนในน้ำแต่พบในตะกอนดินของแม่น้ำท่าจีน คำสำคัญ: แม่น้ำท่าจีน โลหะหนัก เกณฑ์มาตรฐานตะกอนดิน เกณฑ์มาตรฐานคุณภาพน้ำผิวดิน Since 2011, Thailand had a big flood especially central region of country have been affected. Then Tha-chin river was used to a main drainage route for drains a water surplus into Gulf of Thailand. Water surplus that came from minor rivers has many heavy metals from many polluted sources and flow into Tha-chin river. If major river received waste water which contaminate heavy metals for a long time that must be effected to quality of water, accumulation of heavy metals in food chains and may be harmful to aquatic animals and humans. Therefore, this research was studied in concentration of 5 heavy metals for example lead, cadmium, arsenic, mercury and nickel that was examined in sediment soil and water which collected from Tha-chin river from Nakhon Chai Si to estuary of Tha-chin river for studies quantity and accumulation of heavy metals that flow into Tha-chin river. Twenty one and 5 each samples of sediments and surface water were collected from Tha-chin and its 3 inflow canals (Maha Sawat, Pasi Charoen and Maha Chai) analyzed, respectively. Two periods were designed, one in the dry (April) and the rest in the wet (November) of the same year (2012). The results found that Pb, Cd, As, Hg and Ni in the sediment were Lower than sediment standard criteria NOAA while only As was higher than of not sea surface water standard criteria category2, 3 and 4 given by the Pollution Control Department, Thailand. This is an important source of heavy metals found in Tha-chin River. While Cd, was not found in surface water determined but found in Tha-chin’s sediment. Keywords: Tha-chin River, Heavy Metals, Sediment Quality Standards, Surface Water Quality Standards
Keywords: แม่น้ำท่าจีน โลหะหนัก เกณฑ์มาตรฐานตะกอนดิน เกณฑ์มาตรฐานคุณภาพน้ำผิวดิน Tha-chin River, Heavy Metals, Sediment Quality Standards, Surface Water Quality Standards